Fourth International Conference on Current and Future Trends in Bridge Design, Construction and Maintenance proceedings of the 4th International Conference organised on behalf of the Structural and Buildings Board of the Institution of Civil Engineers, and held in Kuala Lumpur, Malaysia, 10-11 October 2005 - Barr, B. (Thomas Telford, 2006)
This book presents the proceedings of the fourth international conference on Current and Future Trends in Bridge Design, Construction and Maintenance, and comprises an extensive reference, an exchange of innovative experience, creative thinking and industry forecasts.